STAT1 gain-of-function variant in a previously healthy patient with disseminated Mycobacterium genavense infection - Kavitha Thiagarajan; Huan Vinh Dong; Caroline Y. Kuo; Timothy J. Thauland; Sheeja Pullarkat; Manish J. Butte; Maria I. Garcia-Lloret; Karin Nielsen-Saines (Journal of Human Immunity, 2026)
Signal transducer and activator of transcription 1 (STAT1) defects present with diverse clinical phenotypes. We describe an unusual genotype/phenotype: disseminated mycobacterial infection without chronic mucocutaneous candidiasis in the context of a pathogenic STAT1 gain-of-function variant (p.Lys388Glu). To our knowledge, this is the first report of such a case.